International Conference on Photonics and Imaging in Biology and Medicine 2017
DOI: 10.1364/pibm.2017.w3a.128
|View full text |Cite
|
Sign up to set email alerts
|

Cell-permeable organic fluorescent probes for live-cell long-term super-resolution imaging reveal lysosome-mitochondrion interactions

Abstract: Two kinds of cell-permeable organic fluorescent probes with high photostability were developed for lysosomes and mitochondria. With these probes, we first observed dynamic physical lysosome-mitochondrion interactions for over 13 min in live-cell dual-color super-resolution imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…To further clarify the resolution of the dye for imaging mitochondria, we obtained a full-width at the half-maximum (FWHM) up to 80 nm under SIM (Fig. 2e-f), which is similar to the Atto 647 mitochondrial dye reported by Han et al (FWHM: 91 nm) 34 . Such results suggest that our dye offers higher resolution and precision for tracking mitochondria under SIM.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…To further clarify the resolution of the dye for imaging mitochondria, we obtained a full-width at the half-maximum (FWHM) up to 80 nm under SIM (Fig. 2e-f), which is similar to the Atto 647 mitochondrial dye reported by Han et al (FWHM: 91 nm) 34 . Such results suggest that our dye offers higher resolution and precision for tracking mitochondria under SIM.…”
Section: Resultssupporting
confidence: 73%
“…Results indicated that the dye had uniform tissue permeability at different depths in living cells. The photobleaching properties of the dye directly affected the monitoring of mitochondrial dynamic processes 33, 34 . Next, we performed a long-term continuous laser (165 s) to stimulate cells in order to monitor the photostability of the dye in the same section of the cell (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 To visualize uptake at high resolution in vivo we labeled lysozyme with very bright and photo-stable fluorophores. 24 We found that uptake of lysozyme and albumin occurred almost exclusively in S1 segments. Although it is somewhat intuitive that uptake of filtered molecules would be higher in the first segment immediately after the glomerulus, the magnitude of the S1/S2 differences was surprising.…”
Section: Discussionmentioning
confidence: 70%
“…Commercially available prelabeled forms of albumin and dextran were used. To label lysozyme we used atto dyes, which are extremely bright and highly photo-stable, 24 thus enabling high-resolution imaging in vivo. Experiments with each ligand were repeated with two different labels to exclude a confounding effect of the fluorophores on uptake.…”
Section: Uptake Of Filtered Proteins By Rme Occurs Almost Exclusivelymentioning
confidence: 99%